Análisis de la derivada de presión en yacimientos naturalmente fracturados con fronteras parcialmente abiertas (2018)
The complexity of conventional resources is increasing, and, therefore an optimum characterization is required. Existing models to study pressure behavior in heterogeneous formations consider only either constant-pressure or closed boundaries. In this paper the pressure derivative for a vertical oil well in a naturally fractured reservoir with a variable open external boundary is analyzed. The parameters governing the pressure response are: final flow rate at the external boundary (qWI) and time at which begins the invasion of fluid at the external boundary (τ), depending on its variability of these parameters, there are three conditions in which the external border acts: closed, partially open and constant-pressure. Lines and characteristic points were identified for each individual case to obtain the fundamental basis to generate the equations for the determination of the parameters that describe this type of reservoirs, such as: qWI and τ. Finally, the TDS technique was extended to interpret pressure tests in these systems. The methodology was satisfactorily verified by solving synthetic examples.